2012
DOI: 10.1001/dmp.2012.19
|View full text |Cite
|
Sign up to set email alerts
|

Triage of Mechanical Ventilation for Pediatric Patients During a Pandemic

Abstract: ABSTRACTObjective: The novel H1N1 influenza pandemic renewed the concern that during a severe pandemic illness, critical care and mechanical ventilation resources will be inadequate to meet the needs of patients. Several published protocols address the need to triage patients for access to ventilator resources. However, to our knowledge, none of these has addressed the pediatric populations.Methods: We used a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…MA was found in more than 60% of critically ill children at admission to the PICU. Commonly used human clinical scoring systems include the Acute Physiology and Chronic Health Evaluation (APACHE), Sequential Organ Failure Assessment (SOFA), Multiple Organ Dysfunction Score, and Simplified Acute Physiology Score (SAPS) in adults and the PIM, PRISM, and PELOD in children (16)(17)(18). The effect of disruption of the integrity of the endothelial barrier is manifested as altered glomerular endothelial permeability in the kidneys, allowing increased amounts of albumin to escape into the glomerular ultrafiltrate.…”
Section: Discussionmentioning
confidence: 99%
“…MA was found in more than 60% of critically ill children at admission to the PICU. Commonly used human clinical scoring systems include the Acute Physiology and Chronic Health Evaluation (APACHE), Sequential Organ Failure Assessment (SOFA), Multiple Organ Dysfunction Score, and Simplified Acute Physiology Score (SAPS) in adults and the PIM, PRISM, and PELOD in children (16)(17)(18). The effect of disruption of the integrity of the endothelial barrier is manifested as altered glomerular endothelial permeability in the kidneys, allowing increased amounts of albumin to escape into the glomerular ultrafiltrate.…”
Section: Discussionmentioning
confidence: 99%
“…Prediction of overall PICU resource use could aid with triage of patients based on bed and nursing availability during a disaster, while prediction of the specific types of and duration of need for resources may optimize allocation of these resources. Ventilator triage is a particular area of interest given the likelihood for shortage with a large influx of patients at high risk for respiratory failure (10,(23)(24)(25). We found that models to predict ventilator need and duration of use performed better than for any other resource.…”
Section: Discussionmentioning
confidence: 87%
“…Although pediatric providers are divided on the use of protocols for triage decisions (7), both the PEMCC Task Force and CHEST guidelines recommend that objective protocols rather than ad hoc clinical judgment be used to determine allocation of limited resources during crises (1,8). Several pediatric illness severity scores have been evaluated for ventilator-triage protocols; however, only the Pediatric Logistic Organ Dysfunction (PELOD) score (9) fulfills all criteria deemed important for use in a triage algorithm (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PELOD-2 was developed and validated to assess the severity of pediatric multiple organ dysfunction syndrome cases [46], based on the PELOD created in 1999 [47] and validated in pandemic settings [48]. The PELOD-2 score, different from its original version, includes mean arterial pressure and lactatemia in cardiovascular dysfunction and does not include liver dysfunction [46].…”
Section: Clinical Criteriamentioning
confidence: 99%